ANALISIS PEMIDANAAN TERHADAP PEMALSUAN SURAT KETERANGAN RAPID TEST ANTIGEN DALAM PUTUSAN PENGADILAN NEGERI JEMBER NOMOR 205/PID.SUS/2021/PN.JMR - Feby Egatri Gulo; R Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
Today, the world is being shaken by a great pandemic called Covid-19 (Corona Virus Disease). One of the countries experiencing the impact of this virus outbreak is Indonesia. So, through this, the Government has the authority to take action in solving a problem, one of which is by showing a Health Certificate of Antigen Rapid Test which is used as a condition for traveling to prevent the spread of the Covid-19 Virus. This study aims to find out how the Criminal Analysis of Counterfeiting of Antigen Rapid Test Certificates in the Jember District Court Decision Number 205/PID.SUS/2021/PN.JMR and evaluate the judge's considerations in deciding this case. The type of research used in this research is normative legal research supported by interview data with experts. Through this research, although forgery has been regulated in the Criminal Code, but regarding the Crime of Counterfeiting Health Certificates, it has not been regulated explicitly. Regarding the sentencing decision, the researcher disagrees because in considering and deciding this criminal case, the judge is considered to be more considerate of the elements and aspects of the occurrence of a crime in aggravating circumstances. So by considering the existing elements, the sentence given is more appropriate by referring to Article 35 jo. Article 51 of Law Number 11 of 2018 concerning ITE as the legal purpose. Researchers suggest that in imposing a sentence on every judicial institution and judge not only decide based on their belief alone, but also based on their responsibilities and values in society.